Determinan Pencegahan Kecurangan Dalam Alokasi Dana Desa - Anak Agung Putu Gede Bagus Arie Susandya; M Doni Permana Putra; I Kadek Bagiana; Meita Risma Cahyani; Ida Ayu Putu Meita Puspa Aristanti (Universitas Muhammadiyah Malang, 2022)
The purpose of this study is to find empirical evidence regarding the effect of competence, morality, integrity, internal control and organizational culture on the fraud prevention in allocation of village funds. The sample in this study are obtained from 148 respondents from village officials in Denpasar. Multiple regression analysis is used to answer the hypothesis in this study. The results of the study find that competence, morality, internal control and organizational culture has a positive effect on fraud prevention. This finding indicates that village officials have responsibilities and want to apply the good village governance principles, transparent, and accountable. Integrity was not able to minimize the occurrence of fraud. The allocation of village funds has a vulnerability in its allocation in infrastructure development in the village. This study uses organizational culture as novelty because there are few articles that examine the allocation of village funds with organizational culture. For further research is expected to examine the characteristics of village heads that can affect the level of fraud prevention in village funds. The village head as the user of village funds is expected to be transparent and responsible in the allocation of village funds.